Puntuación de micronúcleos en células de mucosa bucal de mujeres con cáncer de mama antes y después de la quimioterapia atendidas en iren norte 2016-2017 - Ghiglino Pérez, Pierre André (2017)
The aim of the study was to establish the differences in the micronucleus score in buccal mucosal cells of women with breast cancer before and after chemotherapy treated at IREN NORTE 2016-2017. Buccal mucosa cells from 18 women before chemotherapy and 17 women after chemotherapy were used as samples. The frequency of micronucleated cells of the pre-chemotherapy group was determined at 1.06 ± 1.00, and that of the post-chemotherapy group at 2.24 ± 1.56; besides the frequency of micronuclei of the pre-chemotherapy group was determined at 1.11 ± 1.08, and that of the post-chemotherapy group at 2.41 ± 1.70; also, It was observed variation in the number and size of micronuclei. It is concluded that the frequency of micronucleated cells and the frequency of micronuclei after chemotherapy were significantly higher than before chemotherapy; and that the variation in size and number of micronuclei is associated with the mechanism of action of cytostatics administered during chemotherapy